Estimating the impact of agricultural support on farm price : an analysis of Swedish farm prices - Falkdalen, Maria (SLU/Dept. of Economics, 2019)
Agricultural land prices in Sweden have been increasing steadily since Sweden joined the EU. At the same time, the common agricultural policy of the EU has changed from coupled support given to specific sectors, to decoupled direct support for basic land maintenance. The need to understand the effects of agricultural policy decisions, how prices are determined and what factors are affecting agricultural land values, are therefore highly relevant and interlinked topics.